Leptospirosis in a male patient with systemic lupus erythematosus: a case report - Hira Saleem; Arshad, Azal; Farooq, Mukarram; Sarwar, Shahid; Mansoor, Marium; Farhan Baloch, Maryam (Journal of the Pakistan Medical Association, 2025)
Leptospirosis is an under-reported infection occurring in individuals associated with the agricultural industry. However, its co-existence with Systemic Lupus Erythematosus (SLE) is rare, with only two reported cases present in medical literature. We present the case of a male patient who came with the complaint of fever, right upper quadrant pain, and shortness of breath in an outpatient clinic of Jinnah Hospital, Lahore. Physical examination revealed an erythematous facial rash that worsened on exposure to sunlight. Laboratory findings included impaired renal function tests, pancytopenia, positive ANA and anti-dsDNA antibodies. Imaging revealed lesions in the liver as well as pleural and pericardial effusion. The patient was treated with a combination of antibiotics for leptospirosis infection and corticosteroids for the management of SLE. This case is significant because it highlights the importance of keeping in mind autoimmune conditions as a differential diagnosis when dealing with symptoms of multisystem involvement. MeSH Keywords: Leptospirosis, Systemic lupus erythematosus, Agricultural workers’ diseases, Weil disease, Developing countries.